The Detection and Characterization of QoI-Resistant Didymella rabiei Causing Ascochyta Blight of Chickpea in Montana - Owati, Ayodeji S.; Agindotan, Bright; Pasche, Julie S.; Burrows, Mary (Frontiers in Plant Science, 2017)
Ascochyta blight (AB) of pulse crops (chickpea, field pea, and lentils) causes yield loss in Montana, where 1.2 million acres was planted to pulses in 2016. Pyraclostrobin and azoxystrobin, quinone outside inhibitor (QoI) fungicides, have been the choice of farmers for the management of ascochyta blight in pulses. However, a G143A mutation in the cytochrome b gene has been reported to confer resistance to QoI fungicides. A total of 990 isolates of Ascochyta blight-causing fungi were isolated and screened for QoI resistance. Out of these, 10% were isolated from chickpea, 81% were isolated from dry peas, and 9% isolated from lentil. These were from a survey of grower’s fields and seed lots (chickpea = 17, pea = 131, and lentil = 21) from 23 counties in Montana sent to the Regional Pulse Crop Diagnostic Laboratory, Bozeman, MT for testing. Fungicide-resistant Didymella rabiei isolates were found in one chickpea seed lot each sent from Daniels, McCone and Valley Counties, MT, from seed produced in 2015 and 2016. Multiple alignment analysis of amino acid sequences revealed a missense mutation that replaced the codon for amino acid 143 from GGT to GCT, introducing an amino acid change from glycine to alanine (G143A), which is reportedly associated with QoI resistance. Under greenhouse conditions, disease severity was significantly higher on pyraclostrobin-treated chickpea plants inoculated with QoI-resistant isolates of D. rabiei than sensitive isolates (p-value = 0.001). These results suggest that disease control may be inadequate at locations where resistant isolates are present. D. rabiei-specific polymerase chain reaction primer sets and hydrolysis probes were developed to efficiently discriminate QoI-resistant and - sensitive isolates